2002
DOI: 10.1109/titb.2002.802378
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of fear of flying: a controlled study of imaginal and virtual reality graded exposure therapy

Abstract: The goal of this study was to determine if virtual reality graded exposure therapy (VRGET) was equally efficacious, more efficacious, or less efficacious, than imaginal exposure therapy in the treatment of fear of flying. Thirty participants (Age = 39.8 +/- 9.7) with confirmed DSM-IV diagnosis of specific phobia fear of flying were randomly assigned to one of three groups: VRGET with no physiological feedback (VRGETno), VRGET with physiological feedback (VRGETpm), or systematic desensitization with imaginal ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(94 citation statements)
references
References 13 publications
2
91
0
1
Order By: Relevance
“…The use of VR now allows for measurement of human interaction with realistic dynamic content, albeit within the constraints of the monitoring apparatus. Thus far, heart rate, GSR, and other psychophysiological measures have produced useful results within VR studies examining attention and presence (Pugnetti, Mendozzi, Barberi, Rose, & Attree, 1996;Meehan, Insko, Whitton, & Brooks, 2002) and have been used to enhance treatment effects using a VR biofeedback paradigm for fear-of-flying clients in Wiederhold et al (2002). Even within the confines of a 3-tesla magnetic-imaging device with the user's head in a fixed position, humans can navigate and interact in a VR world with specialized nonmetal displays and interface devices.…”
Section: Integration Of Vr With Physiological Monitoring and Brain Immentioning
confidence: 99%
“…The use of VR now allows for measurement of human interaction with realistic dynamic content, albeit within the constraints of the monitoring apparatus. Thus far, heart rate, GSR, and other psychophysiological measures have produced useful results within VR studies examining attention and presence (Pugnetti, Mendozzi, Barberi, Rose, & Attree, 1996;Meehan, Insko, Whitton, & Brooks, 2002) and have been used to enhance treatment effects using a VR biofeedback paradigm for fear-of-flying clients in Wiederhold et al (2002). Even within the confines of a 3-tesla magnetic-imaging device with the user's head in a fixed position, humans can navigate and interact in a VR world with specialized nonmetal displays and interface devices.…”
Section: Integration Of Vr With Physiological Monitoring and Brain Immentioning
confidence: 99%
“…Unlike exposure using the imagination, patients are engaged by several of their senses, heightening the realism of the context. Unlike exposure "in vivo", patients are in a safe, confidential place with the therapist in complete control [15]. Finally, it is much more difficult to control the variables in real-life situations than in VR environments.…”
Section: Virtual Reality As a Clinical Toolmentioning
confidence: 99%
“…However, the flexibility of virtual environments can also enable therapists to create, control, and modify realistic scenarios for the treatment of phobias (for a review, see Riva, 2005). Wiederhold and colleagues showed that graded exposures to flying experiences in virtual reality were effective in helping phobic participants to fly without the aid of medication or alcohol (Wiederhold et al, 2002).…”
Section: Phobiasmentioning
confidence: 99%